Peningkatan Aktifitas Belajar Peserta Didik Sekolah Dasar pada Pembelajaran IPS melalui Metode Pembelajaran Inkuiri - Bone, Matilda Pia; Lio, Stefanus (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2023)
This study aimed to determine whether the use of inquiry learning method can increase students' learning activities in social studies learning in elementary schools. This research approach was qualitative, using classroom action research method. The research procedure refers to the Lewis method in the form of a cycle. Each cycle consists of four main activities, namely planning, implementing, evaluating, and improving plans. The results of the study showed that the application of the inquiry learning method in social studies learning can increase students' learning activities. So, it can be concluded that the inquiry learning method is a learning method that can develop student learning activities, which has an impact on increasing student learning outcomes. Therefore, the application of the inquiry learning method is highly recommended for use in social studies learning in elementary schools.